The Impact of Workplace Dust Exposure and Mask Usage on Pulmonary Function in Construction Environments - Sumardiyono, Sumardiyono; Maria Paskanita Widjanarti; Farhana Syahrotun Nisa Suratna; Bachtiar Chahyadhi; Reni Wijayanti; Rachmawati Prihantina Fauzi; Yeremia Rante Ada’; Yunita Dwi Puspitasari; Agathara, Reidiatama Aviano (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: The chance of respiratory diseases among workers participating in toll road construction projects is, for example, higher because of non-organic dust. Therefore, this study aims to evaluate the level of lung capacity experienced by the workers by exposing them to dust and wearing masks. Methods: This cross-sectional study investigated toll road projects in Central Java and Yogyakarta and randomly selected workers from different strata of construction companies. The volume Air Sampler estimated dust concentration, while the pulmonary function test included spirometry. All data were analyzed using two-way MANOVA. Results and Discussion: The multivariate analysis of variance showed that workers exposed to dust exceeding the Threshold Limit Value (TLV) had significantly reduced FEV1 and FVC averages (p < 0.001). The averages of FEV1 and FVC increased more considerably in mask users than non-users, indicating mask usage's benefits. The decline in lung function was smaller in mask users, with FEV1 (95% CI: 0.080–0.321) and FVC (95% CI: 0.071–0.404). A reduction in walking distance also demonstrated significance to the decrease in FVC. Conclusion: They found that dust in construction declines lung capacity, but wearing masks provides some protection. However, such impact continues even after stopping wearing masks, thus stressing the importance of correct mask usage and staff training. Subsequent research must investigate dust interaction and various types of masks to enhance Indonesian workers’ health.